Propyrisulfuron plus cyhalofop butyl as one-shot herbicides provide high weed control efficiency and net economic performance in mechanically transplanted rice - Zhang, Zichang; Wang, Hongchun; Gu, Tao; Cao, Jingjing; Lou, Yuanlai; Li, Gui (Frontiers in Plant Science, 2023)
Propyrisulfuron is a novel pyrimidinylsulfonylurea herbicide with good activity for controlling annual weed in rice fields. To evaluate the economic performance of propyrisulfuron, a field study was conducted in 2021 and 2022 on a farm of the Jiangsu Academy of Agricultural Sciences, China. Eight different herbicide treatments were employed, including CB (cyhalofop butyl), Py (propyrisulfuron), CBPy (cyhalofop butyl plus propyrisulfuron), PrBe 3, PrBe 10, and PrBe 3+PrBe 10 (pretilachlor plus bensulfuron applied at different times [at 3 (PrBe 3) and 10 (PrBe 10) d] or sequentially, respectively), 2PrBe+PeCBBz (pretilachlor plus bensulfuron [applied sequentially] followed by penoxsulam plus cyhalofop butyl plus bentazone), 2PrBe+MeCBBz (pretilachlor plus bensulfuron [applied sequentially] followed by metamifop plus cyhalofop butyl plus bentazone), along with weed-free and nontreated weedy check treatments. Herbicide treatments did not cause visual phytotoxicity to rice, and bending and leaf rolling were not observed. Only the two propyrisulfuron treatments had temporary negative effects on rice height, but rice recovered quickly. Compared with the weed-free treatment, CBPy did not affect rice tiller number or dry matter accumulation. Compared with the nontreated weedy check, herbicide treatments reduced total weed density by 29.4% to 99.1% and dry biomass by 32.2% to 98.7%. The CBPy treatment provided the best weed control, reducing weed density and biomass by 96.7% and 95.9% in 2021 and 97.4% and 95.6% in 2022, respectively. Rice grain yield was not significantly different between CBPy and the weed-free treatment in either year. Economic analysis showed that CBPy provided the highest net profit, followed by that in 2PrBe+PeCBBz and 2PrBe+MeCBBz, with the lowest net profit in the nontreated weedy check. Thus, CBPy provides good weed control and could be promoted in mechanically transplanted rice fields in China.